Electrochemical sensor for sulfite determination based on a nanostructured copper-salen film modified electrode - Dadamos, Tony R. L. [UNESP]; Teixeira, Marcos F. S. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
The electrochemical preparation described herein involved the electrocatalytic oxidation of sulfite on a platinum electrode modified with nanostructured copper salen (salen=N,N'-ethylenebis(salicylideneiminato)) polymer films. The complex was prepared and electropolymerized at a platinum electrode in a 0.1 mol L-1 solution of tetrabutylammonium perchlorate in acetonitrile by cyclic voltammetry between 0 and 1.4V vs. SCE. After cycling the modified electrode in a 0.50 mol L-1 KCI solution, the estimated surface concentration was found to be equal to 2.2 x 10(-9) Mol cm(-2). This is a typical behavior of an electrode surface immobilized with a redox couple that can usually be considered as a reversible single-electron reduction/oxidation of the copper(II)/copper(III) couple. The potential peaks of the modified electrode in the electrolyte solution (aqueous) containing the different anions increase with the decrease of the ionic radius, demonstrating that the counter-ions influence the voltammetric behavior of the sensor. The potential peak was found to be linearly dependent upon the ratio [ionic charge]/[ionic radius]. The oxidation of the sulfite anion was performed at the platinum electrode at +0.9V vs. SCE. However, a significant decrease in the overpotential (+0.45V) was obtained while using the sensor, which minimized the effect of oxidizable interferences. A plot of the anodic current vs. the sulfite concentration for chronoamperometry (potential fixed = +0.45V) at the sensor was linear in the 4.0 x 10(-6) to 6.9 x 10(-5) mol L-1 concentration range and the concentration limit was 1.2 x 10(-6) mol L-1. The reaction order with respect to sulfite was determined by the slope of the logarithm of the current vs. the logarithm of the sulfite concentration. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Modified electrode; Copper-salen complex; Nanostructured polymer; Amperometric detection; Sulfite